Regional Design: Discretionary Approaches to Planning in the Netherlands - Balz, Verena (A+BE | Architecture and the Built Environment, 2019)
In the 1980s, planning approaches in European regions have changed as a result of increasing attention to regional spatial developments and a diminishing reliance on government-led statutory planning schemes. Emerging new approaches, often called spatial planning, shifted the focus from planning predefined territories to the planning of spatial networks, which stretch across multiple administrative boundaries. In this specific context of spatial planning, new decision-making approaches have emerged, involving coalitions of plan actors from multiple tiers and levels of government as well as market and civil actors. In near absence of formally approved statutory planning frameworks, broad involvement became a way to legitimize planning decisions and, at the same time, amass organisational capacity for their implementation. A decision-making approach that has gained prominence in the context of spatial planning in the Netherlands is regional design. Building upon a tradition of using design-led approaches in planning, expectations on the performances of regional design in the realm of spatial planning are high. Regional design is thought to be an imaginative and creative practice, which leads to planning innovation. It is expected to enhance the spatial quality that planning strategies and projects produce. Regional design is also assumed to perform in governance settings. It is supposed to clarify political options, forge societal alliances, and remove conflict around planning solutions during early moments of decision-making and speeding up their implementation in this way. Despite these high and varied expectations, an in-depth understanding of the interrelations between regional design and spatial planning is not yet achieved. The rich body of professional writing on regional design in the Netherlands is often focused on single practices. It is fragmented. The body of scholarly writing dedicated to regional design is small and has deficiencies for this reason. A particular knowledge gap is caused by a one-sided perspective on the performances of regional design. Most existing analyses focus on the expected impacts of regional-design practices on planning decisions. Various theoretical notions on spatial planning and governance are used to assert these expectations. A reversed approach, in which the impact of aspects of prevailing planning frameworks on design practice is of concern, is missing. Performances of regional design practice are often considered disappointing and sometimes even averse, due to this lack of indepth understanding. Research aims and questions In consideration of the above sketched background, the main aim of this research is to develop a more comprehensive understanding of interrelations between regional design and spatial planning. There are three secondary aims. This research seeks to first integrate notions from various domains and fields for an enhanced transdisciplinary understanding of regional design. Whereas many Dutch regional design initiatives refer to multiple objectives simultaneously, it remains unclear how regional design-led approaches influence planning decisions. A second sub-aim of the research is to develop a distinction of regional design practices in relation to spatial planning frameworks and to improve the prediction of key performances based upon this distinction. It remains also unclear how planning frameworks influence the performances of design. A third sub-aim is to arrive at an enhanced understanding of key aspects of spatial planning frameworks that determine performances. Aims and secondary aims are reflected in the following research questions: How do the interrelations between regional design and spatial planning influence the performances of design? What are key performances of regional design in the realm of spatial planning? How can these key performances be analysed? What aspects of spatial planning frameworks influence the performances of regional design? How can these aspects of spatial planning frameworks be analysed? Research approach Regional design is a collaborative social practice, which involves a multitude of actors, and has a concern about the complex built environment. Expectations that are triggered by the practice are divers and have rarely been studied comprehensively. The above research questions were therefore investigated by means of an exploratory case-study analysis, which is an appropriate research methodology to stabilize and detail propositions in a context of uncertainty. In the first in-depth single case-study key performances of regional design in the realm of spatial planning were investigated. A second multiple case-studies analysis was used to compare interrelations between regional-design practices and spatial-planning frameworks. The study enhanced a greater understanding of the aspects of frameworks that influence the divers performances. Analysed regional-design practices were selected by their principle concern about urbanisation, a relation with Dutch national spatial plans, and their prominence in the Dutch planning discourse. All practices were developed between the mid-1980s, when regional design first appeared as a distinguished discipline in the Netherlands, and the 2010s, when the most recent Dutch national plan that could be considered at the time of this dissertation was published. The majority of empirical analyses was based on publicly available policy documents. Particular attention was given to geographic representations. Besides drawing on empirical evidence, the analysis involved a continuous process of theory formation, which used notions from the fields of architecture and urban design, spatial planning and territorial governance. Results of the exploratory case-study analysis were published in the form of peer-reviewed book chapters and journal articles. The content of these publications that form the Chapters 3 to 7 of this thesis, is summarized below. Chapter 3 – From concepts to projects: Stedenbaan, the Netherlands Chapter 3 was earlier published as a co-authored chapter in the book Transit Oriented Development: Making it Happen (Balz and Schrijnen, 2009). The chapter presents an initial review of a regional-design practice that was conducted between 2005 and 2007 by South Wing Studio (Atelier Zuidvleugel). This was a publicly funded policy institute concerned with regional spatial planning and design in the Southern part of the Dutch Randstad region. In the chapter, it is argued that the practice has contributed to establishing the Stedenbaan project, a regional transitoriented development strategy, on the political agenda of governance arrangements in the region. It was decisive to involve plan actors in building the argument for the strategy. This observation has led to the initial proposition of this dissertation: that regional design is an argumentative practice that performs in planning decisionmaking. Chapter 4 - Regional design in the context of fragmented territorial governance: South Wing Studio Chapter 4, earlier published as a co-authored journal article in European Planning Studies (Balz and Zonneveld, 2015), presents results of an in-depth single casestudy analysis that answers the questions: what are key performances of regional design in the realm of spatial planning?, and how can these key performances be analysed? The chapter first establishes a theoretically grounded analytical framework that positions regional design in the context of spatial concepts. Spatial concepts are perceptions of geographies that actors pursue during planning decision-making. It is argued that regional design assists in the building of arguments for spatial planning interventions through structuring the reservoirs of analytical knowledge and normative values that these concepts incorporate. As in the initial review of regional design, the South Wing Studio’s contribution to the formation of the Stedenbaan strategy is under investigation. The empirical analysis identifies performances in the form of shifts in policy argumentation from analytical verification to the normative validation of the strategy. The research also highlighted a pragmatic use of design. Analysis showed that design argumentation involved a strong consideration of capacities of actors for planning in territories. Insights led to an adaptation of the original analytical framework: spatial concepts became perceived to have not only an analytical and normative dimension, but also an organisational one. Chapter 5 - Transformations of planning rationalities: Changing spaces for governance in recent Dutch planning The second multiple case-studies analysis in this dissertation sought to answer the following questions: what aspects of spatial planning frameworks influence the performances of regional design?, and how can these aspects of spatial planning frameworks be analysed? Chapter 5 of this thesis, first published as a co-authored journal article in Planning Theory & Practice (Balz and Zonneveld, 2018), presents one part of this analysis. Building upon the earlier established notions on dimensions of spatial concepts as a context of regional design, as well as additional theoretical notions on in particular argumentative planning, it is first argued that the ambiguity of spatial concepts shapes room for interpretation in spatial-planning decisionmaking and thus influences territorial governance. In the main empirical section of the chapter, spatial concepts that have been used in Dutch national plans between the 1980s and the 2010s are assessed on their degree of ambiguity. Analysis led to a detailed and critical reading of the transformations of spatial rationales that were used to justify Dutch national spatial planning over time. On a theoretical level, the chapter proposes a methodological approach to investigate such changes. It contributes to the discussion on how governance responses to the use of geographies in planning decision-making can be explained. Chapter 6 - Regional design: Discretionary approaches to regional planning in the Netherlands Chapter 6, earlier published as a sole-authored journal article in Planning Theory (Balz, 2018), presents the overall outcomes of the multiple case-studies analysis and addresses the central proposition of this dissertation: that regional design is a form of discretionary action and is meant to qualify spatial planning guidance by means of reflecting upon its implications for particular regions. Building upon the earlier established analytical framework and additional notions from design theory, it is first argued that, depending on the ambiguity of premediated spatial concepts, regional design proposals have fundamentally different interrelations with these concepts. They either are a refinement of analytical knowledge, normative values, and territorial instructions that concepts incorporate, or a challenge to these reservoirs of meaning. Performances of regional design differ consequently. Regional design either evolves as a pragmatic approach where actors commonly operationalise an agreed-upon planning framework by applying it to a particular spatial situation or forms an advocacy where actors disagree on a premediated framework and use design proposals to call for its revision. These findings are supported by an analysis of interrelations between four regional-design practices and the earlier mentioned analysed spatial concepts. In the discussion section, the relevance of insights for Dutch national planning is reviewed. Theoretically relevant results concern the use of regional design in the realm of spatial planning. It is concluded that regional design mediates between a collaborative and strategic rationale of spatial planning through its engagement with both, general and specific perceptions of regions and areas. Chapter 7 - The institutionalisation of a creative practice: Changing positions and roles of regional design in Dutch national planning Chapter 7 was earlier accepted for publication as a co-authored chapter in the forthcoming book Shaping Regional Futures: Designing and Visioning in Governance Rescaling (Balz and Zonneveld, 2019). It investigates the organisational implications of perceiving regional design as a form of discretion. In discretion, there is a distinction between discretionary action, which criticises existing rules, and discretionary control, which determines if criticism should lead to a revision of rules. A distance between actors with roles in these functions is required to enhance legitimacy and accountability. In the empirical section of the chapter, the distinction is used for an analysis of a broad range of regional design practices that were used in Dutch national spatial planning during the period between the 1980s and 2010s. The analysis elaborates who initiated practices, who conducted design, and who judged the quality and relevance of design outcomes for planning decisions. In addition, the analysis identifies patterns in the institutionalisation of regional design by the repetition of practices, adoption in formal policies and enshrinement in dedicated organisations. The chapter demonstrates how institutionalisation has facilitated a shift from using regional design as a form of advocacy, oriented at nurturing a critical public audience of planning, to one of pragmatic use, oriented at the implementation of projects of national importance. The conclusions emphasize a need for discernible roles in regional design practice when it is used in discretion. Conclusion Chapter 7 was earlier accepted for publication as a co-authored chapter in the forthcoming book Shaping Regional Futures: Designing and Visioning in Governance Rescaling (Balz and Zonneveld, 2019). It investigates the organisational implications of perceiving regional design as a form of discretion. In discretion, there is a distinction between discretionary action, which criticises existing rules, and discretionary control, which determines if criticism should lead to a revision of rules. A distance between actors with roles in these functions is required to enhance legitimacy and accountability. In the empirical section of the chapter, the distinction is used for an analysis of a broad range of regional design practices that were used in Dutch national spatial planning during the period between the 1980s and 2010s. The analysis elaborates who initiated practices, who conducted design, and who judged the quality and relevance of design outcomes for planning decisions. In addition, the analysis identifies patterns in the institutionalisation of regional design by the repetition of practices, adoption in formal policies and enshrinement in dedicated organisations. The chapter demonstrates how institutionalisation has facilitated a shift from using regional design as a form of advocacy, oriented at nurturing a critical public audience of planning, to one of pragmatic use, oriented at the implementation of projects of national importance. The conclusions emphasize a need for discernible roles in regional design practice when it is used in discretion. This dissertation has evolved as an exploratory case-study research. Its first and most important outcome is in the above listed notions: on (1) key performances that regional design has in the realm of spatial planning and on (2) aspects of spatial planning frameworks that influence these performances. Through building an analytical framework that assesses these propositions, it contributes to an enhanced understanding of interrelations between regional design and spatial planning. A second outcome of the thesis is the results of the empirical analysis which is centred on the use of regional design in the realm of Dutch national spatial planning between the 1980s and 2010s. It is argued that the institutionalisation of practices has favoured a rather one-sided, pragmatic use of regional design. As a result, distances between actors with roles in discretionary action and control became undiscernible. The criticism that the thesis poses is meant to inform reflection on the involvement of regional design in Dutch national planning. It calls for a more comprehensive, accountable and legitimate future use. There are limitations to critical positions. The empirical analysis took account of a selection of regional design practices only, notably ones with a principle concern about urbanisation. The analysis also does not fully consider the Dutch national government’s additional and less pragmatic efforts to stimulate good regional design practice, e.g. through providing funding for academic research and publications that critically discuss the use of regional design. A third outcome of this dissertation is the recommended directions for future research. The thesis argues that regional design equals discretion and thus attempts to mediate between generally accepted and applicable spatial planning principles and spatial rationales linked to problems in particular local situations. An enhanced understanding of such attempts first requires a more sophisticated assessment of how perceptions of geographies transform as they are used – how ambiguous spatial concepts turn into detailed designs and vice versa. The ambiguity or softness of spatial planning frameworks is a prominent issue in scholarly discussion on how spatial planning evolves in a context of decentralisation and deregulation. However, there are no benchmark methodologies to detect such ambiguity or softness. The thesis developed an analytical approach to deduce the ambiguity of geographic perceptions from the amount and relative degree of detail of notions in their analytical, normative and organisational dimensions. It requires further validation. Scholars in discretion have highlighted the importance of professional organizations in controlling rule-building. On the grounds of these notions, this thesis argues that the role of regional design professionals in spatial-planning decision-making requires deeper understanding. In particular the values and norms that professionals pursue need more attention. Due to a tradition of using design-led approaches in the realm of planning, regional design is a frequently used practice in the Netherlands. However, similar approaches occur in other (European) countries, albeit in a less prominent and visible way. As planning systems and cultures differ in countries, a comparative perspective on these may lead to a deeper understanding of not just the practices themselves, but also of ways how spatial development finds attention in spatial planning elsewhere. An implicit proposition developed is that flexibility, in the form of ambiguous geographies, relates to the creativity of planning and its ability to find novel and innovative solutions to problems on the ground. This proposition calls for a broader integration of theoretical knowledge about planning and design.